2004
DOI: 10.1200/jco.2004.03.118
|View full text |Cite
|
Sign up to set email alerts
|

p53, p21, pRB, and p16 Expression Predict Clinical Outcome in Cystectomy With Bladder Cancer

Abstract: Although altered expression of each of the four cell cycle regulators is associated with bladder cancer outcome in patients undergoing radical cystectomy, p53 is the strongest predictor, followed by p21, suggesting a more pivotal role of the p53/p21 pathway in bladder cancer progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
228
5
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 292 publications
(264 citation statements)
references
References 22 publications
23
228
5
8
Order By: Relevance
“…In retrospective studies using tumour samples from radical cystectomy specimens, nuclear accumulation of p21 was detected in 64% of specimens and was an independent predictor of tumour recurrence and survival when concomitantly assessed with tumour grade, stage, lymph node status and p53 status. 22,26 P27 overexpression in human cells has been shown to result in cell cycle arrest in the G1 phase. In patients with muscleinvasive disease treated with radical cystectomy, p27 was the second most powerful cell cycle regulator after p53 for prediction of bladder cancer recurrence and survival.…”
Section: Biomarkers Of Prognosis and Therapeutic Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…In retrospective studies using tumour samples from radical cystectomy specimens, nuclear accumulation of p21 was detected in 64% of specimens and was an independent predictor of tumour recurrence and survival when concomitantly assessed with tumour grade, stage, lymph node status and p53 status. 22,26 P27 overexpression in human cells has been shown to result in cell cycle arrest in the G1 phase. In patients with muscleinvasive disease treated with radical cystectomy, p27 was the second most powerful cell cycle regulator after p53 for prediction of bladder cancer recurrence and survival.…”
Section: Biomarkers Of Prognosis and Therapeutic Efficacymentioning
confidence: 99%
“…Many studies support the association of p53 nuclear accumulation with tumour stage, lymphovascular invasion, lymph node metastasis, high-grade tumour, disease recurrence and bladder cancer specific death. [19][20][21][22][23][24][25] However, a metaanalysis by Malats that reviewed 117 studies spanning 10 years concluded that there is insufficient evidence to support that changes in p53 can be a marker of outcome in patients with bladder cancer. 32 A clinical trial investigated whether alterations of immunohistochemical p53 nuclear expression could prospectively identify patients that would benefit from the administration of adjuvant MVAC chemotherapy.…”
Section: Biomarkers Of Prognosis and Therapeutic Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…2 Bladder cancer has been shown to resist programmed cell death both with altered expression of pro-and antiapoptotic proteins. [3][4][5] Survivin is a member of the inhibitor of apoptosis (IAP) gene family that has been found to control mitotic progression and induces changes in gene expression that are associated with tumor cell invasiveness. 6,7 Survivin mRNA is selectively expressed during embryonic and fetal development, 8 becomes undetectable or expressed at low levels in most differentiated normal adult tissues, and is overexpressed in human cancers.…”
mentioning
confidence: 99%
“…21 Alterations of the p53 and RB regulatory pathways are predominantly seen in clinically aggressive high-grade bladder cancer. [22][23][24][25][26][27][28] *P-values of Kaplan-Meier log-rank test.…”
Section: Discussionmentioning
confidence: 99%